2003
DOI: 10.1111/j.1365-2621.2003.tb07037.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of K‐Casein Deglycosylation on the Acid Coagulability of Milk

Abstract: The relationship between the content of N-acetylneuraminic acid residues of micellar -casein and acid coagulability of milk was investigated. At 30 °C, partial deglycosylation of micellar -casein does not significantly affect the content of micellar proteins, micellar surface charge, and micellar solvation. Casein micelles modified by the release of part of the N-acetylneuraminic acid residues showed a shorter acid gelation time, a higher rate of gel strengthening, and a higher final firmness. This enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…Difference in the rennin-gel structure for deglycosylated casein was also observed with the observation of larger cluster and pores in comparison with native casein. With the same objective, Cases et al (2003) deglycosylated also casein micelles by neuraminidase and studied the physico-chemical properties and their ability to form acid gel. They indicated that partial deglycosylation (∼85%) did not significantly affect neither the partition of molecules of casein between aqueous and micellar phases nor their charge and hydration.…”
Section: Deglycosylationmentioning
confidence: 99%
“…Difference in the rennin-gel structure for deglycosylated casein was also observed with the observation of larger cluster and pores in comparison with native casein. With the same objective, Cases et al (2003) deglycosylated also casein micelles by neuraminidase and studied the physico-chemical properties and their ability to form acid gel. They indicated that partial deglycosylation (∼85%) did not significantly affect neither the partition of molecules of casein between aqueous and micellar phases nor their charge and hydration.…”
Section: Deglycosylationmentioning
confidence: 99%
“…Cases et al (2003) found that partial deglycosylation with neuraminidase had little effect on micellar surface charge and solvation but caused a decrease in acid gelation time, a higher rate of gel firming, and a higher final firmness. Because this step does not involve k-casein cleavage, a lesser or different effect might be expected.…”
Section: Functional Significancementioning
confidence: 96%
“…Due to the fact that glycosylation only occurs in the hydrophilic C-terminus of k-casein, treatment of milk with soluble or immobilized neuraminidase is efficient in removing virtually all NANA from milk (Mehaia and Cheryan, 1983;Mehaia, 1987;Cases et al, 2003). Treatment of milk with neuraminidase had only a small, but significant, effect on its heat stability (Robitaille and Ayers, 1995).…”
Section: Enzymatic Deglycosylation Of Milk Proteinsmentioning
confidence: 99%